A Calcium Mediated Mechanism Coordinating Vascular Smooth Muscle Cell Adhesion During KCl Activation - Huang, Huang; Sun, Zhe; Hill, Michael A.; Meininger, Gerald A. (Frontiers in Physiology, 2018)
Physical coupling of vascular smooth muscle cells (VSMCs) to extracellular matrix proteins (ECM) by integrins is required for efficient mechanotransduction. Integrin adhesion receptors are essential for normal vascular function and defective integrin signaling is associated with cardiovascular disease. However, far less is known about mechanism of integrin activation in VSMCs as it relates to vasoregulation. Previous work from our laboratory demonstrated that increased VSMC stiffness, induced by the vasoconstrictor Angiotensin II (AII), is coordinated with enhanced adhesion to fibronectin (FN) indicating an important role for adhesion in contraction. However, the mechanism of this coordination is not fully understood. In this study, we hypothesized that enhanced adhesion in response to AII was mediated by integrin activation through an inside-out signaling pathway linked to increases in intracellular Ca2+ ([Ca2+]i). By using atomic force microscopy (AFM) with an anti-a5 antibody coated AFM probe, we confirmed that cell stiffness was increased by AII, but we observed no changes in adhesion to the anti-a5 antibody. This indicated that increases in cell adhesion to FN induced by AII was occurring through an integrin activation process, as increased membrane integrin expression/receptor density would have been accompanied by increased adhesion to the anti-a5 antibody. Further studies with KCl and BAPTA-AM were used to modulate the level of [Ca2+]i. After KCl, VSMCs showed a rapid transient increase in cell stiffness as well as cell adhesion to FN, and these two events were synchronized with superimposed transient increases in the level of [Ca2+]i, which was measured using the Ca2+ indicator, fluo-4. These changes were not abolished in VSMCs pretreated with the myosin light chain kinase inhibitor, ML-7. In contrast, VSMCs incubated with intracellular calcium chelator, BAPTA-AM, showed reductions in stiffness and cell adhesion to FN as well as decreased [Ca2+]i. These data suggest that in VSMCs integrin activation is linked to signaling events tied to levels of [Ca2+]i and it is not dependent on events downstream of contraction. These findings provide additional evidence to support a role for adhesion in VSMC contraction and suggest that following cell contractile activation, that adhesion may be regulated in tandem with the contractile event.